إشكالية السببية بين المعتزلة والأشاعرة - دريسي, زكية (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2021)
ان موضوع السببية يعتبر من الموضوعات الهامة في مجال الفكر الفلسفي عبر مختلف العصور .وربما لا توجد مسألة لقيت عناية من الفلاسفة مثل مالقته مسألة السببية ، فبدونها تستحيل كل فلسفة في المعرفة ،وتبطل كل فلسفة من فلسفات الوجود، إذ أن مسألة السببية على حد قول أحد المفكرين ،هو الرابطة الوحيدة التي تربط العالم بالموجودات بحيث اذا رفضنا تلك الرابطة ،فسوف يتردى العالم الى فوضى ونظرا لهذه الأهمية حول هذه الفكرة فقد إنشغل الفلاسفة على إختلاف مدارسهم ومذاهبهم وفرقهم ،بفكرة السببية بقصد تفسيرها ،حيث أننا نجد علم الكلام الاسلامي ،وخاصة الفرقتين المعتزلة و الأشاعرة قد اهتموا بهذه المسألة ودرسوها ،حيث نجد لكل فرقة رأيها الخاص فالسببية عند المعتزلة هي العلاقة الضرورية التي تربط السبب بالمسبب ،وهذا طبعا بحججهم (التوليد ،القرآن اما بالنسبة للأشاعرة فهي ترى عكس ذلك ،وان العلاقة التي تربط السبب بالمسبب غير ضرورية ،وإنها مجرد عادة من خلال عملية التكرار The issue of causation is considered one of the important topics in the field of philosophical thought throughout the various ages. Perhaps there is no issue that has received attention from philosophers like it is related to the issue of causation, without which every philosophy of knowledge becomes impossible, and every philosophy of existence is nullified, since the issue of causation, according to someone Thinkers, it is the only bond that links the world to the foundations, so that if we reject that link, the world will descend into chaos and due to this importance around this idea, philosophers of different schools, sects and groups have been preoccupied with the idea of causation with the intention of explaining it, as we find the science of Islamic theology, especially the two Mu'tazilite groups. And the Ash'ari have paid attention to this issue and studied it, as we find for each group its own opinion, as for the Mu'tazila, causation is the necessary relationship that links the cause to the cause, and this of course with their arguments (generation, the Qur’an as for the Ash'ari, they see the opposite, and the relationship that links the cause to the cause is unnecessary, And it's just a habit through the process of iteration
Keywords: السببية /العلة / المعتزلة / الاشاعرة / العادة causation / illness / Mu'tazila / Ash'ari / habit